2009
DOI: 10.1002/joc.1838
|View full text |Cite
|
Sign up to set email alerts
|

Winter precipitation intensity and ENSO/PDO variability in the Willamette Valley of Oregon

Abstract: There is growing concern about the effects of inter-annual climatic variability, such as the El-Niño Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO), on regional hydrology and water resources. We analysed patterns of wintertime precipitation intensity, using both simple intensity and number of heavy precipitation days per year, for eight stations in northwestern Oregon's Willamette Valley for the period 1972-2006, and examined the separate and combined influence of ENSO and PDO on precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…These observations were consistent with temperature and precipitation observations (Neal et al, 2002). Praskievicz and Chang (2009) demonstrated that the relation between PDO and precipitation intensity in Oregon is negative and strongest in January and March in the Willamette Valley. This region of Oregon is a transition zone between +/-ENSO effects and the moderating effects of ENSO/PDO.…”
Section: Precipitationsupporting
confidence: 90%
“…These observations were consistent with temperature and precipitation observations (Neal et al, 2002). Praskievicz and Chang (2009) demonstrated that the relation between PDO and precipitation intensity in Oregon is negative and strongest in January and March in the Willamette Valley. This region of Oregon is a transition zone between +/-ENSO effects and the moderating effects of ENSO/PDO.…”
Section: Precipitationsupporting
confidence: 90%
“…Oregon precipitation intensity and volume are shown to vary with climate oscillations, and correlate with ENSO and PDO phase changes [27,53]. It is unclear whether this trend will continue in the future, but as atmospheric rivers that bring heavy precipitation into the area may become more pronounced under warming scenarios, such a trend might likely to continue in the future [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to hypothesize that changes to precipitation intensity in Oregon may be an early indication of climate change, since projections do indicate a shift and intensification in the North Pacific storm track that drives Oregon's precipitation regime [27]. Downscaled climate simulations for the Pacific Northwest of North America show an increase in up to 0.3 mm in daily precipitation in the Portland area if the storm track changes [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved continuous temporal resolution may provide a more accurate predictor of avian species richness and abundance than simply maximum NDVI of one or two images, particularly in an area undergoing rapid land clearing and subsequent construction. Similarly to using a synthetic variable such as NDVI to represent vegetative cover and primary productivity, the Oceanic Niño Index (ONI), a measure of ENSO that utilizes ocean buoys to measure sea temperature, provides a synthetic climate variable that may represent future patterns if climate change models are accurate (Praskievicz and Chang, 2009;Chen et al, 2011;Todd et al, 2011). Although it is clear that no single weather variable, such as temperature or precipitation, is adequate to predict changes in productivity or bird populations, a composite climate variable that summarizes changes in temperature as well as precipitation, such as the strength of the ENSO, may have stronger predictive power.…”
Section: Introductionmentioning
confidence: 99%